(untitled) (Journal of Contemporary Philology, 2018)
Review of the Proceedings "How are you?" – philological student conference 2017, V. Blaževska, M. Veličkovska, V. Dizdarević, S. Grujoska, M. Efremov, Skopje, Blaže Koneski Faculty of Philology, 2018